CD4+ T cell heterogeneity in gestational age and preeclampsia using single-cell RNA sequencing - Tsuda, Sayaka; Shichino, Shigeyuki; Tilburgs, Tamara; Shima, Tomoko; Morita, Keiko; Yamaki-Ushijima, Akemi; Roskin, Krishna; Tomura, Michio; Sameshima, Azusa; Saito, Shigeru; Nakashima, Akitoshi (Frontiers in Immunology, 2024)
A balance between pro-inflammatory decidual CD4 + T cells and FOXP3 + regulatory T cells (FOXP3 + Tregs) is important for maintaining fetomaternal tolerance. Using single-cell RNAsequencing and T cell receptor repertoire analysis, we determined that diversity and clonality of decidual CD4 + T cell subsets depend on gestational age. Th1/Th2 intermediate and Th1 subsets of CD4 + T cells were clonally expanded in both early and late gestation, whereas FOXP3 + Tregs were scRNAseq of decidual T cells clonally expanded in late gestation. Th1/Th2 intermediate and FOXP3 + Treg subsets showed altered gene expression in preeclampsia (PE) compared to healthy late gestation. The Th1/Th2 intermediate subset exhibited elevated levels of cytotoxicity-related gene expression in PE. Moreover, increased Treg exhaustion was observed in the PE group, and FOXP3 + Treg subcluster analysis revealed that the effector Treg like subset drove the Treg exhaustion signatures in PE. The Th1/Th2 intermediate and effector Treg like subsets are possible inflammation-driving subsets in PE.